When the following quadratic equation is written in standard form, what is the value of "c" for the equation x2 + 4x = 3.
We will use the concept of the general form of quadratic equation in order to find the value of c.
Answer: x2 + 4x - 3 = 0 is in the general form of the given quadratic equation x2 + 4x = 3 with c = -3.
Let us see how we will use the concept of the general form of quadratic equation in order to find the value of c.
The general form of a quadratic equation is represented by ax2 + bx + c.
We have been given the equation in the form of x2 + 4x = 3.
In order to convert the equation in the general form, we have to transpose 3 to the left-hand side.
On transposing 3 we will get x2 + 4x - 3 = 0 and this quadratic equation is in general form.
Hence, on comparison of x2 + 4x - 3 = 0 with ax2 + bx + c = 0 we get, a = 1, b = 4, c = -3.